Analyzing Tinder Through User Motivations and Experiences Among Indian Young Adults - Nair, Ananthu; K., Padmakumar (Indian Journal of Marketing, 2020)
Traditional conventions of match making and meeting potential partners were replaced by the Internet almost three decades ago. Today, mobile dating apps (MDAs) have become the preferred choice for young adults to meet new people. The trend which originally started in the Western world has eventually caught up with India as well. In the absence of any published studies in the Indian scenario, the present study examined the consumption of the dating app, Tinder. In addition to understanding the motivations for Tinder use, user perceptions and experiences were also explored. The findings of the study are suggestive of a male-dominated user base. The study also found that physical appearance was the most popular factor which influenced a right swipe, which justifies the user interface of the app. In the light of the Tinder Motives Scales (TMS), the study attempted to understand the motivations for Tinder use. Tinder use for entertainment was found to be the most popular motive. The study also revealed that an overwhelming majority of Tinder users did not believe in the possibility of finding a long-term romantic partner. Using these insights, theoretical and managerial implications are also discussed, one of which pertains to how the scope for Tinder extends beyond just bringing people together or finding potential partners.